Standard specification for Steel Wire, Deformed, for Concrete Reinforcement (American Society of Testing Materials, 2007)
This specification covers deformed steel wire which has been cold-worked by drawing, rolling, or both drawing and rolling, to be used as produced, or in fabricated form, for the reinforcement of concrete in sizes having nominal crosssectional areas not less than 6.45 mm2[0.01 in.2].